Acclimation to cold and warm temperatures is associated with differential expression of male carp blood proteins involved in acute phase and stress responses, and lipid metabolism. Issue 76 (May 2018) - Dietrich, Mariola A.; Hliwa, Piotr; Adamek, Mikołaj; Steinhagen, Dieter; Karol, Halina; Ciereszko, Andrzej
Abstract: The environmental temperature affects plasma biochemical indicators, antioxidant status and hematological and immunological parameters in fish. So far, only single blood proteins have been identified in response to temperature changes. The aim of this study was to compare the proteome of carp blood plasma from males acclimated to warm (30 °C) and cold (10 °C) temperatures by two-dimensional differential gel electrophoresis followed by MALDI-TOF/TOF mass spectrometry. A total of 47 spots were found to be differentially regulated by temperature (>1.2-fold change, p < 0.05): 25 protein spots were more abundant in warm-acclimated males and 22 were enriched in cold-acclimated males. The majority of differentially regulated proteins were associated with acute phase response signalling involved in: i) activation of the complement system (complement C3-H1), ii) neutralization of proteolytic enzymes (inter-alpha inhibitor H3, fetuin, serpinA1, antithrombin, alpha2-macroglobulin), iii) scavenging of free hemoglobin and radicals (haptoglobin, Wap65 kDa), iv) clot-formation (fibrinogen beta and alpha chain, T-kininogen) and v) the host's immune response modulation (ApoA1 and ApoA2). However, quite different sets of these proteins or proteoforms were involved in response to cold and warm temperatures. In addition, cold acclimation seems to be related to the proteins involved in lipid metabolism (apolipoproteins A and 14 kDa) and stress response (corticosteroid binding globulin). We discovered a strongly regulated protein Cap31 upon cold acclimation, which can serve as a potential blood biomarker of cold response in carp. These studies significantly extend our knowledge concerning mechanisms underlying thermal adaptation in poikilotherms. Highlights: Proteomic approach was used to identify acclimation-related proteins. Thermal acclimation is associated with changes in carp blood proteome. 9 and 12 proteins were upregulated to warm and cold acclimation, respectively. Acute phase and stress response, lipid metabolism are associated with thermal adaptation. Cap31 was upregulated upon adaptation to cold temperature.